Cardiopulmonary toxicity of pulmonary exposure to occupationally relevant zinc oxide nanoparticles. Issue 6 (September 2014) - Chuang, Hsiao-Chi; Juan, Hung-Tzu; Chang, Chun-Nung; Yan, Yuan-Horng; Yuan, Tzu-Hsuen; Wang, Jyh-Seng; Chen, Hao-Cheng; Hwang, Yaw-Huei; Lee, Chii-Hong; Cheng, Tsun-Jen
Abstract Exposure to zinc oxide (ZnO) metal fumes is linked to adverse human health effects; however, the hazards of ZnO nanoparticles (ZnONPs) remain unclear. To determine pulmonary exposure to occupationally relevant ZnONPs cause cardiopulmonary injury, Sprague-Dawley rats were exposed to ZnONPs via intratracheal (IT) instillation and inhalation. The relationship between intrapulmonary zinc levels and pulmonary oxidative-inflammatory responses 72 h after ZnONP instillation was determined in bronchoalveolar lavage fluid (BALF). Instilled ZnONPs altered zinc balance and increased the levels of total cells, neutrophils, lactate dehydrogenase (LDH) and total protein in BALF and 8-hydroxy-2′-deoxyguanosine (8-OHdG) in blood after 72 h. The ZnONPs accumulated predominantly in the lungs over 24 h, and trivial amounts of zinc were determined in the heart, liver, kidneys and blood. Furthermore, the inflammatory-oxidative responses induced by occupationally relevant levels of 1.1 and 4.9 mg/m3 of ZnONP inhalation for 2 weeks were determined in BALF and blood at 1, 7 and 30 days post-exposure. Histopathological examinations of the rat lungs and hearts were performed. Inhalation of ZnONP caused an inflammatory cytological profile. The total cell, neutrophil, LDH and total protein levels were acutely increased in the BALF, and there was an inflammatory pathology in the lungs. There were subchronic levels of white blood cells, granulocytes and 8-OHdG in the blood. Cardiac inflammation and the development of fibrosis were detected 7 days after exposure. Degeneration and necrosis of the myocardium were detected 30 days after exposure. The results demonstrate that ZnONPs cause cardiopulmonary impairments. These findings highlight the occupational health effects for ZnONP-exposed workers.